The Relationship of Knowledge Level with the Event of Serumen Prop in the Elderly at Puskesmas Lubuk Buaya Padang - Seres Triola; Heti Lestari; Rhandyka Rafli; Haves Ashan (Budapest International Research and Critics University, 2022)
Cerumen prop has a fairly high prevalence and can affect all ages. In the elderly, the cerumen becomes dry due to atrophy of the cerumen glands and the hair in the ear canal becomes coarser. This results in higher cerumen prop levels in elderly patients. The purpose of this study was to determine the relationship between the level of knowledge and the incidence of cerumen prop in the elderly at the Lubuk Buaya Padang Health Center. The scope of this research is health science ENT-KL (Ear Nose Throat Head and Neck surgery) and the elderly. The research was conducted in January 2022. The type of research is analytic. The affordable population in this study were the elderly at the Lubuk Buaya Padang Health Center as many as 37 samples with concecutive sampling technique. Univariate data analysis is presented in the form of frequency distribution and bivariate analysis using chi-square test. The incidence of cerumen prop in the elderly was 19 (51.4%), the highest level of knowledge was bad, namely in 22 (59.5%) elderly, and there was a relationship between the level of knowledge and the incidence of cerumen prop in the elderly at the Lubuk Buaya Padang Health Center (p = 0.032). The number of elderly who experienced cerumen prop was not much different from the number of elderly who did not experience cerumen prop, the highest level of knowledge was poor, and there was a relationship between the level of knowledge and the incidence of cerumen prop in the elderly at the Lubuk Buaya Public Health Center, Padang.